Navigating Research Trends in Support and Stigma: A Bibliometric Analysis and Future Research Agenda - Hajdini, Johana; Dirsehan, Taskın; Iaia, Lea (European Scientific Journal, ESJ, 2025)
Aim and Scope: Stigma has changed and evolved over time with the progress of knowledge and humanity. The negative outcomes of stigma, such as social isolation, exclusion, poor treatment adherence, and limited access to healthcare services, have garnered interest among research communities. The complex nature of stigma as a socially constructed phenomenon and its continuous evolution raises the need to track changes and fit future interventions. Methods: We synthesize extant research on stigma and support through a bibliometric analysis of 257 articles investigating the stigma phenomenon. The study contributes to a comprehensive understanding and helps the translation of research findings into action to drive social change and evidence-based policies. Findings: Our analysis revealed a growing interest in the domain in recent years. The results show six main directions of research: (1) stigma as a barrier, (2) cultural contexts of stigma, (3) perceived stigma and coping strategies, (4) stories of experiences of stigma, (5) action to mitigate stigma, and (6) community stigma. Conclusions: This study has theoretical and practical implications, in highlighting the multidimensionality of stigma and the need for multi-level policies to raise awareness among communities.